Leishmaniasis recidivans in Ethiopia: cutaneous and mucocutaneous features - Dassoni, Federica; Daba, Frehiwot; Naafs, Bernard; Morrone, Aldo (The Journal of Infection in Developing Countries, 2017)
Cutaneous leishmaniasis (CL) is endemic in Ethiopia. An unusual clinical form of this disease is leishmaniasis recidivans (LR), a prolonged, relapsing form of cutaneous leishmaniasis resembling tuberculosis of the skin that may persist for many years with a chronic and relapsing course. This rare variant has been shown to be caused by Leishmania tropica species in the Old World and by Leishmania braziliensis, Leishmania amazonensis, Leishmania panamensis, and Leishmania guyanensis in the New World, as reported in various studies. To our knowledge, there are no reports from Ethiopia, and mucocutaneous involvement of LR has not been described to date. This was a retrospective analysis of the patients seen at the Italian Dermatological Center in Mekelle on the Tigrean highlands over a three-year period (2008–2011). Seven patients with typical clinical features of LR were seen. Two of them presented with signs of mucosal involvement. To date, Leishmania aethiopica is shown to be the only species causing CL that is endemic in the Ethiopian highlands. Therefore, it had to be assumed that the lesions in these patients were caused by this species. The aims of this communication are to report, for the first time, the presence of LR, most likely due to Leishmania aethiopica, in Ethiopia, and to report mucosal involvement in this rare clinical form of CL.